Bentuk Tindak Tutur Asertif Suku Bajo Parumaan dan Suku Tana AI dalam Interaksi Jual Beli di Pasar Nangahale - Ardiansah Andika Fajar; Trisnawati Bura; Bertholomeus Jawa Bhaga (Institut Pendidikan Alfatah Mataram, 2025)
This study aims to describe the forms of assertive speech acts used by the Bajo Parumaan and Tana Ai tribes in buying and selling interactions at Nangahale Market. This research employs a qualitative descriptive method with a pragmatic approach. The data consist of utterances produced by sellers and buyers, collected through observation, participant observation, recording, and note-taking techniques. The collected data were analyzed through data reduction, data presentation, and conclusion drawing. The results show that assertive speech acts are highly dominant in trading interactions at Nangahale Market. The forms of assertive speech acts identified include informing, suggesting, boasting, complaining, and refusing. Informing is the most frequently used assertive speech act, particularly in conveying information about prices, types, and conditions of goods. Suggesting and boasting are commonly used by sellers as persuasive strategies to attract buyers, while complaining and refusing are more often expressed by buyers as responses to prices or product quality. These findings indicate that assertive speech acts play an important role in shaping communication dynamics and negotiation processes in traditional market transactions